Improving The Financial and Asset Management of The Al-Manar Mosque As A Form of Implementing SDG's 17: Peningkatan Pengelolaan Keuangan dan Aset Masjid Al-Manar Sebagai Bentuk Penerapan SDG’s 17 - Izza Noor Abidin, Fityan; Biduri, Sarwenda; Wahyuning Tyas, Erinda; Tri Amanda, Risha (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Al-Manar Mosque faces challenges in financial and asset management that are still done manually, which causes inaccuracies in financial records and reports, as well as difficulties in monitoring assets. This service program aims to improve the management of mosque finances and assets through the application of digital-based systems, such as the use of the Sias Masjid web and integrated spreadsheets. The method used in this program is a waterfall approach which includes problem analysis, training in the use of digital systems, and periodic evaluation. The implementation results show an increase in transparency and accountability of financial management, with financial reports that are more accurate and can be accessed in real-time by worshipers. Asset management has also become more structured with a digital inventory that allows monitoring of asset conditions and maintenance schedules. The program not only improves the mosque's operational efficiency but also strengthens community trust in mosque management. The program is in line with SDG's 17, which aims to strengthen global partnerships in sustainable development, particularly in the context of transparent and accountable management